Recreational angler and stakeholder perceptions of policy changes to recreational fishery management: the case of red snapper devolution in the Gulf of Mexico - Thomas G Moorman; Daniel Morris; Steven B Scyphers; Ryan D. Williamson; Kelly H Dunning (Ecology and Society)
In 2020, management of a prized recreational sportfish species, Lutjanus campechanus (red snapper), underwent a landmark change in the Gulf of Mexico of the United States: from federal management at the national level to a more localized, state level management. This policy change is based on the idea that localized management, informed by greater understanding of the context of the social-ecological system, enhances resilience. But how do fisheries stakeholders see this policy change? Our research asks how fishery stakeholders’ perceptions, especially recreational fishermen’s, vary across those who supported and did not support this change in management, known as Amendment 50 to the Gulf of Mexico Reef Fish Management Plan. We analyzed n = 2206 stakeholder comments using mixed methods and qualitative coding. Our thematic analysis found that 40% of comments supported devolved state management, 3% opposed it, and 57% could not be classified because the comment did not explicitly state support or opposition. In this paper, we only analyze the comments that explicitly support (40%) or oppose (3%) state management. We found that supporters of more localized fisheries management believe that it is characterized by (1) greater flexibility in management, (2) more trustworthiness, (3) better recreational access, and (4) trustworthy science. We argue that these four beliefs, analyzed through inductive methods, form a locally accepted and context-dependent model of resilient management for one of the most iconic recreational fisheries in the United States, in one of its fastest growing coastal regions. This model, built from these four beliefs, are connected by stakeholder trust in government. Understanding how to enhance stakeholder, especially recreational fishermen, trust in government has important implications for sectors beyond fishery management.